2022
DOI: 10.12659/ajcr.936505
|View full text |Cite
|
Sign up to set email alerts
|

Selinexor in Patients from Argentina with Multiple Myeloma Treated with Multiple Prior Therapies: A Case Series

Abstract: Case series Patients: Male, 72-year-old • Female, 59-year-old • Female, 62-year-old Final Diagnosis: Multiple myeloma Symptoms: Anemia • hypercalcemia • lytic bone lesions Medication: Selinexor Clinical Procedure: — Specialty: Hematology Objective: Unusual setting of medical care Background: Numerous treatment options are available for patients with multiple myeloma (MM). Because of the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…In addition to the STOMP study (Table 3) [62], selinexor‐Vd has been investigated in two studies of heavily pretreated patients with RRMM (Table 4) [77, 78]. Reflecting the efficacy seen with selinexor‐dexamethasone in this later‐relapse setting, both studies showed notable response rates, with three of the 10 patients across the studies achieving ≥VGPR.…”
Section: Clinical Studies Of Selinexor In Multiple Myelomamentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the STOMP study (Table 3) [62], selinexor‐Vd has been investigated in two studies of heavily pretreated patients with RRMM (Table 4) [77, 78]. Reflecting the efficacy seen with selinexor‐dexamethasone in this later‐relapse setting, both studies showed notable response rates, with three of the 10 patients across the studies achieving ≥VGPR.…”
Section: Clinical Studies Of Selinexor In Multiple Myelomamentioning
confidence: 99%
“…or standard-risk cytogenetics, the benefit of selinexor-Vd versus Vd was maintained in terms of ORR (high-risk 79% vs. 58%; standard-risk 75% vs. 65%) and PFS (high-risk: median 12.9 vs. 8.6 months, HR 0.73; standard-risk: median 16.6 vs. 9.5 months, HR 0.61), albeit that there was evidence of the poor prognostic impact of high-risk cytogenetics on outcomes in both arms [63] In addition to the STOMP study (Table 3) [62], selinexor-Vd has been investigated in two studies of heavily pretreated patients with RRMM (Table 4) [77,78]. Reflecting the efficacy seen with selinexordexamethasone in this later-relapse setting, both studies showed notable response rates, with three of the 10 patients across the studies achieving ≥VGPR.…”
Section: Selinexor-based Triplet Regimens For Rrmmmentioning
confidence: 99%